Aspectos humanistas: a afetividade entre professor e alunos - Castro, Fernando Henrique dos Reis [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This work looks for figure out how and why it's important the teacher have a good relationship with their students and how this influences on learning process and its quality. For that, a case study was carried out in a qualitative perspective to verify such influence, as stated by the referenced theories. It is part of a situation observed in high school classrooms about the feeling observed in some students by a certain mathematics teacher of their last year of Elementary School. Analyzing the collected data related to this situation, it was considered important to investigate the affectivity between teacher and his students, their way of acting towards them, and the meaning of these attitude in the learning process. This research was carried out in a school in the interior of São Paulo, during November 2013 and November 2015, and counted on the collaboration of the management team from that school. The results of this research showed that the good relationship between the teacher and his students had a positive influence on student learning, as the theory on the subject points out

Este trabalho visa investigar como e por que é importante que o professor tenha uma boa relação com seus alunos e como essa relação influencia no processo de aprendizagem. Para tanto, foi realizado um estudo de caso em uma perspectiva qualitativa para verificar tal influência, como afirmam as teorias referenciadas. Parte-se de uma situação observada em sala de aula de Ensino Médio sobre o sentimento observado em alguns alunos por um determinado professor de Matemática do último ano do Ensino Fundamental. Analisando essa situação, considerou-se importante investigar a afetividade entre professor e alunos, sua forma de agir para com eles e o significado dessas atitudes no processo de aprendizagem. Esta investigação ocorreu em uma escola no interior de São Paulo, durante os meses de novembro de 2013 e novembro de 2015 e contou com a colaboração da equipe gestora desta escola. Os resultados desta pesquisa mostram que a boa relação entre o professor e seus alunos influenciou positivamente a aprendizagem dos estudantes
Keywords: Matemática - Estudo e ensino; Aprendizagem; Educação humanistica; Afetividade; Psicologia da aprendizagem; Mathematics Study and teaching